PEMODELAN DETERMINAN TINGKAT PENGANGGURAN TERDIDIK DI KABUPATEN SUMBAWA BARAT MENGGUNAKAN METODE REGRESI - Dita Agustina; Novi Kadewi Sumbawati; Abdul Rahim (Jurnal Ekonomi & Bisnis, 2023)
This study aims to examine the determinants of the level of educated unemployment in West Sumbawa Regency in 2012-2021, which consists of population and minimum wages using the regression method. The type of this study was associative with the type of data used quantitative data in the form of population data, minimum wages and educated unemployment in West Sumbawa Regency for the last ten years, namely 2012-2021. The data used in this study were obtained from documents or archives that have been published on the website of the West Sumbawa Regency Central Statistics Agency. The collected data was analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient test (R2). The results of this study showed that the population had no partial effect on the level of educated unemployment, while the minimum wage has a negative and significant effect on the level of educated unemployment in West Sumbawa Regency in 2012-2021. Simultaneously, population size and minimum wage had a significant effect on the level of educated unemployment in West Sumbawa Regency in 2012-2021. The ability of the variables population size and minimum wage to influence changes in the level of educated unemployment in West Sumbawa Regency in 2012-2021 is 42.8%, while the remaining 57.2% is influenced by other variables outside this research model, such as the education level, wages, age, gender, work experience, training, marital status, and area of residence.